Ageing process - Eleey, Peter ca. 20. Jh; Huberman, Anthony 1975-; Le Feuvre, Lisa 1950-; Heiser, Jörg 1968-; Herbert, Martin; Manacorda, Francesco 1974-; McClean, Daniel; Miessen, Markus 1978-; Roelstraete, Dieter 1972-; Simon, Joshua 1979-; Toufic, Jalal 1962-; Wood, Brian Kuan (Sternberg Press, 2015)
Ageing Process, Lara Favaretto's first monograph, documents the artist's works from the 1990s to her most recent installations presented in the 2015 exhibition "Good Luck!" at MAXXI in Rome. Structured like a manual, this volume accompanies entries on her works with essays by critics and experts from various disciplines who tackle themes complementary but not directly connected to the artist's practice. Favaretto, who also edited the book, explains: "I decided not to follow any chronological or alphabetical order, but to instead suggest a unified discourse by making the reading experience flow as smoothly as possible, following an underground web of references between the texts that would elude any scansion dictated by the sequence of dates or letters."